Origin and evolution of the panarthropod head – A palaeobiological and developmental perspective - Ortega-Hernández, Javier; Janssen, Ralf; Budd, Graham E. (Arthropod structure & development, 2017)
The panarthropod head represents a complex body region that has evolved through the integration and functional specialization of the anterior appendage-bearing segments. Advances in the developmental biology of diverse extant organisms have led to a substantial clarity regarding the relationships of segmental homology between Onychophora (velvet worms), Tardigrada (water bears), and Euarthropoda (e.g. arachnids, myriapods, crustaceans, hexapods). The improved understanding of the segmental organization in panarthropods offers a novel perspective for interpreting the ubiquitous Cambrian fossil record of these successful animals. A combined palaeobiological and developmental approach to the study of the panarthropod head through deep time leads us to propose a consensus hypothesis for the intricate evolutionary history of this important tagma. The contribution of exceptionally preserved brains in Cambrian fossils – together with the recognition of segmentally informative morphological characters – illuminate the polarity for major anatomical features. The euarthropod stem-lineage provides a detailed view of the step-wise acquisition of critical characters, including the origin of a multiappendicular head formed by the fusion of several segments, and the transformation of the ancestral protocerebral limb pair into the labrum, following the postero-ventral migration of the mouth opening. Stem-group onychophorans demonstrate an independent ventral migration of the mouth and development of a multisegmented head, as well as the differentiation of the deutocerebral limbs as expressed in extant representatives. The anterior organization of crown-group Tardigrada retains several ancestral features, such as an anterior-facing mouth and one-segmented head. The proposed model aims to clarify contentious issues on the evolution of the panarthropod head, and lays the foundation from which to further address this complex subject in the future. •Developmental and palaeobiological data pertinent to the (Pan)arthropod head problem are reviewed.•Cambrian fossils illuminate the ancestral segmental organization of Euarthropoda, Tardigrada and Onychophora.•Raptorial appendages have evolved convergently throughout the evolutionary history of Panarthropoda.•Cambrian fossils reflect the parallel evolution of a ventral mouth and multisegmented head in Euarthropoda and Onychophora.•The origin of a fused protocerebrum most likely predates the diversification of crown-group Panarthropoda.